2021
DOI: 10.21037/tp-20-198
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene ApaI and FokI polymorphisms and its association with inflammation and oxidative stress in vitamin D sufficient Caucasian Spanish children

Abstract: Background: Vitamin D has gone from being just one vitamin to being an important prohormone with multiple effects on different tissue types. The mechanism of action of the active form or calcitriol is mediated by the intracellular vitamin D receptor (VDR). The interaction of the VDR with calcitriol modulates the expression of target genes involved in cell proliferation and cytokine production. Several studies have explored the effects of vitamin D deficiency in inflammatory disorders. Furthermore, some mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Interestingly, recent data suggested that genetic variations of VDR are associated with changes in metabolic, inflammatory, and oxidative stress parameters in children, providing evidence of how specific VDR polymorphisms may play a role in general susceptibility or protection to cardiometabolic risk and diseases through these clinical biomarkers [ 101 ].…”
Section: Vitamin D and Genetic Determinantsmentioning
confidence: 99%
“…Interestingly, recent data suggested that genetic variations of VDR are associated with changes in metabolic, inflammatory, and oxidative stress parameters in children, providing evidence of how specific VDR polymorphisms may play a role in general susceptibility or protection to cardiometabolic risk and diseases through these clinical biomarkers [ 101 ].…”
Section: Vitamin D and Genetic Determinantsmentioning
confidence: 99%
“…However, the frequency of the “B-a-T-F” haplotype of vitamin D receptor gene polymorphisms was significantly greater in control patients compared to CL patients and could be protective against CL, as the odds of having the haplotype were lower among CL patients compared to controls, suggesting that this haplotype may have the potential to protect against cutaneous leishmaniasis susceptibility These results revealed that the presence of the “A” allele in ApaI SNP of VDR and “B-A-T-F” haplotype increases the susceptibility to CL, while “a” allele and “B-a-T-F ” haplotype may have potential protection against CL and these are novel findings which have not been reported before. A previous study found that the A allele in the ApaI SNP was related to lower serum TNF- levels [ 48 ]. TNF-α, IFN-λ, and other proinflammatory cytokines may influence the outcome of leishmaniasis because they play an important role in macrophage activation and activate inducible nitric oxide synthase.…”
Section: Discussionmentioning
confidence: 99%
“…The SNPs ApaI and BsmI do not affect the amino acid sequence or structure of the VDR protein because they are located in intron 8 at the 3′ end of the VDR gene. However, the ApaI and BsmI SNPs could affect the alternative splicing of VDR mRNA, alter mRNA stability, and modulate the transcription of the VDR gene [40,41]. The TaqI polymorphism is located in exon 9 at the 3′ end of the human VDR gene and does not alter the VDR protein but causes a synonymous change due to a nucleotide substitution.…”
Section: Discussionmentioning
confidence: 99%